Blockade of tachykinin NK1/NK2 receptors in the brain attenuates the activation of corticotrophin-releasing hormone neurones in the hypothalamic paraventricular nucleus and the sympathoadrenal and pituitary-adrenal responses to formalin-induced pain in the rat - Culman, Juraj; Das, G.; Ohlendorf, C.; Haass, Markus; Maser-Gluth, Christiane; Zuhayra, M.; Zhao, Y.; Itoi, K. (Journal of neuroendocrinology, 2010)
Evidence from pharmacological studies has implicated substance P (SP), a natural ligand of tachykinin NK(1) receptors which can also interact with NK(2) receptors, in the generation of pressor and tachycardic responses to stress. Using selective blockade of brain NK(1) and NK(2) receptors, we tested in conscious rats the hypothesis that SP initiates, within the neuronal brain circuits, the sympathoadrenal, hypothalamic-pituitary-adrenal (HPA) and behavioural responses to noxious stimuli. Formalin injected s.c. through a chronically implanted catheter in the area of the lower leg was used as a pain stimulus. Rats were pretreated i.c.v. with vehicle or the selective, nonpeptide antagonists of tachykinin NK(1) and NK(2) receptors, RP 67580 and SR 48968, respectively. Ten minutes thereafter, formalin was injected s.c. and the cardiovascular responses were recorded, plasma concentrations of catecholamines, adrenocorticotrophic hormone (ACTH) and corticosterone were determined and the expression of the inducible transcription factor c-Fos in the paraventricular (PVN) and supraoptic nuclei was detected to identify neurones which were activated during pain stimulation. Blockade of NK(1) and NK(2) receptors attenuated the formalin-induced increases in mean arterial pressure and heart rate, adrenaline and ACTH concentrations in plasma, and completely abolished the pain-induced c-Fos expression in corticotrophin-releasing hormone neurones localised in the parvocellular division of the PVN. The results obtained provide pharmacological evidence that tachykinins, most probably SP, act as mediators within the neuronal circuits linked to the initiation and control of the cardiovascular, sympathoadrenal, HPA and behavioural responses to pain stimuli and provide an excitatory input to corticotrophin-releasing hormone neurones in the PVN to activate the HPA axis. Our data demonstrating the inhibition of the complex response pattern to noxious stimuli and stress are consistent with the proposed anxiolytic and antidepressant activity of NK(1) and NK(2) receptor antagonists.
Gesehen am 21.07.2023